Structural relationship of child behavior and its evaluation during dental treatment - Shinohara, Sachio; Nomura, Yoshiaki; Shingyouchi, Kaori; Takase, Atsuko; Ide, Masamichi; Moriyasu, Katsuya; Idaira, Yayoi; Takahashi, Tomohide; Yamada, Yumiko; Aoyagi, Yoko; Asada, Yoshinobu (Journal of Oral Science, 2005)
The present study uses structural equation modeling to explore the structural relationship of child behavior type and its evaluation during dental treatment. The study population consisted of 33 children at their first visit to a pediatric dentist at the Dental Hospital of Tsurumi University. Child behavior was evaluated by the Frankl Behavior Rating Scale and the behavior evaluation scale developed by Kurosu. Factor analysis extracted 3 behavior types: escape, self-defense, and facial expression. The path diagram of structural relationships between child behavior and the Frankl Behavior Rating Scale indicated that facial expression had the strongest correlation to the Frankl Behavior Rating Scale. (J. Oral Sci. 47, 91-96, 2005)